MOTIVASI KERJA, KOMPETENSI, DISIPLIN KERJA, KEPEMIMPINAN, DAN KINERJA PEGAWAI - Harapan Tua, Raja Putri Yulia, Zaili Rusli, (Jurnal Ilmu Administrasi Negara, 2019)
Work Motivation, Competence, Work Discipline, Leadership, and Employee Performance. This study aims to encourage work, competence, work discipline and leadership on employee performance in Rumbai District, Riau Pekanbaru City. The sampling method uses census sampling and sample transmission using an error rate of 5%. The author conducts research based on data collection techniques through questionnaires. The analysis of the data that I use is the quantification of data through multiple linear regression analysis with t test and partial test R2 and collecting data processed with the help of the SPSS 22.0 statistical program. The results of the study show partially and simultaneously that five variables have a positive effect on employee performance. In addition, it can be seen from where the R value of 0.965 and R2 of 0.924 or 92.4% of the dependent variable independent variables and 7.6% variables are influenced by other variables not examined in this study.